Vessel day scheme and tuna catch in the Pacific Island Region - Champa Bati Dutta; Mark Ivekolia; Debasish Kumar Das (Asian Development Bank Institute (ADBI), 2023)
The Pacific Island nations heavily rely on the tuna fishery for government revenue and economic growth. Since the conversion of some nations to the Vessel Days Scheme (VDS) from the fishing Quota system, the region's domestic catch has significantly increased. VDS has stimulated economic return but raised concerns about tuna overexploitation. We apply Difference in Difference to investigate the effects of the VDS on domestic catch levels in the Pacific region using data on domestic catches from 17 Pacific countries from 2000 to 2020. The estimated result indicates that tuna catches increased by more than 200% in VDS nations relative to non-VDS nations in the region.
Keywords: F55; O11; O13; O56; Q22; Q27; Q28; 330; Vessel Day Scheme; tuna fishery; total fleet catch; Pacific island countries